Microfluidic platform for negative enrichment of circulating tumor cells - Sajay, Bhuvanendran Nair Gourikutty (2016)
Negative enrichment is the preferred approach for tumor cell isolation as it does not rely on biomarker expression. However, size-based negative enrichment methods suffer from well-known recovery/purity trade-off. Non-size based methods have a number of processing steps that lead to compounded cell loss due to extensive sample processing and handling which result in a low recovery efficiency. We present a method that performs negative enrichment in two steps from 2 ml of whole blood in a total assay processing time of 60 min. This negative enrichment method employs upstream immunomagnetic depletion to deplete CD45-positive WBCs followed by a microfabricated filter membrane to perform chemical-free RBC depletion and target cells isolation. Experiments of spiking two cell lines, MCF-7 and NCI-H1975, in the whole blood show an average of >90 % cell recovery over a range of spiked cell numbers. We also successfully recovered circulating tumor cells from 15 cancer patient samples.